Systematic Literature Review on Quarter Life Crisis in Final Year Students: A Study of the Role of Social Support, Career Decisions, and Resilience - Alamsyah, Digi; Widhiastuti, Hardani; Dewi , Rusmalia (Journal Corner of Education, Linguistics, and Literature, 2025)
The phenomenon of quarter-life crisis (QLC) among final-year students has become an increasingly important issue in developmental psychology studies, considering that the transition to the workforce and adulthood is often accompanied by complex psychosocial pressures. This research aims to systematically examine the role of social support, career decision-making, and resilience towards QLC through the Systematic Literature Review (SLR) method on 16 scientific articles published between 2018 and 2024 and indexed in reputable databases such as Scopus and ScienceDirect. The analysis was conducted with the help of VOSviewer software to map the relationships between keywords and main themes. The study results indicate that social support and maturity in career decisions contribute to reducing QLC pressure, while resilience proves to be an important mediator in helping students adapt psychologically. Bibliometric visualisation identifies two dominant approaches in the literature, namely psychosocial (focusing on mental health and study-to-work transitions) and reflective-spiritual (value-based and meaning of life). These findings emphasise the value of developing holistic campus interventions based on positive psychology to strengthen the resilience of final-year students in facing life transitions